The Role of Organizational Culture in Improving Principal Leadership Effectiveness and Performance: A Literature Review - Pulungan, LIlik Hidayat; Elfrianto, Elfrianto; Tanjung, Bahdin Nur (Jurnal Riset Ilmu Pendidikan, 2024)
Organizational culture plays an important role in supporting the effectiveness of principal leadership and performance. This article aims to review various studies that discuss the relationship between organizational culture, leadership, and principal performance. Through a literature review approach, this study analyzes the results of previous studies to find the relationship between these elements. A strong organizational culture has been shown to have a significant impact on the effectiveness of principal leadership, because it can create a conducive work environment, increase collaboration, and strengthen the commitment of organizational members to common goals. In addition, an inclusive and learning-oriented organizational culture supports principals in managing operational and strategic challenges, including managing conflict and resistance to change. This study also revealed that transformational leadership plays a major role in leveraging organizational culture to create innovation and improve performance. Principals who succeed in building a positive organizational culture often demonstrate flexibility and ability to face the dynamics of modern education. By understanding the core values ??of organizational culture, principals can build harmonious relationships with teachers, staff, and students, thereby creating a better learning environment. The results of the study also show that a weak organizational culture can be an obstacle to achieving educational goals. In this condition, the principal needs to take strategic steps to strengthen the organizational culture, including involving all school members in the decision-making process and increasing teacher participation in curriculum development. A strong organizational culture not only improves the performance of the principal but also has a positive impact on student learning outcomes and staff job satisfaction. This study makes an important contribution to understanding the relationship between organizational culture, leadership, and principal performance. By integrating findings from various studies, this article provides recommendations for principals, policy makers, and educational researchers to focus on strengthening organizational culture as a primary strategy in improving the quality of education. This study also opens up opportunities for further research that can explore specific ways to integrate organizational culture with adaptive leadership styles